A New Design Protoype of Safety System on Traffic Light using Hydraulic Limiters Zebra Cross Automatic - Rahmad Rizki; Suwarno Suwarno (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Medan city is the third largest metropolitan city in Indonesia. Problems that occur in big cities, especially in the city of Medan itself, include the level of congestion and the level of violations of traffic signs which are quite high and the constraints of emergency vehicles on duty such as ambulances, fire engines and other emergency vehicles, especially on traffic lights. This paper described Emergency vehicles that will build a Security System Using Barriers on Zebra Crosses, especially in Microcontroller-Based Traffic Light. This system uses the RFID component RC522 as an emergency vehicle detector photodiode and laser diode as vehicle detection components above the zebra cross so that the barrier does not damage the vehicle. Servo motor as a barrier gate drive and Arduino Uno R3 as a component where each input command is received to be processed. Where if the emergency vehicle is passing through a traffic light with a red light, then the light will turn green. With this system, the emergency vehicle on duty is not late to its destination and the driver cannot break through the road divider when the red light is on and does not disturb pedestrians. feet to cross The application of the system is designed to be connected directly to Arduino so that the input signal can be processed and can produce the expected output on the performance of the system, namely the servo motor, and 6 LEDs on the traffic light 2 intersections.